2018
DOI: 10.3390/jmse6030102
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Active Structural Control of Offshore Wind Turbines Considering Damage Development

Abstract: High flexibility of new offshore wind turbines (OWT) makes them vulnerable since they are subjected to large environmental loadings, wind turbine excitations and seismic loadings. A control system capable of mitigating undesired vibrations with the potential of modifying its structural properties depending on time-variant loadings and damage development can effectively enhance serviceability and fatigue lifetime of turbine systems. In the present paper, a model for offshore wind turbine systems equipped with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Thus, it is conventionally required that the extreme response of building structures be restricted within an acceptable level [31,32]. Otherwise, associated measures should be implemented for vibration reduction and control of the dynamic systems [33][34][35][36].…”
Section: Estimation Of Structural Extreme Responsementioning
confidence: 99%
“…Thus, it is conventionally required that the extreme response of building structures be restricted within an acceptable level [31,32]. Otherwise, associated measures should be implemented for vibration reduction and control of the dynamic systems [33][34][35][36].…”
Section: Estimation Of Structural Extreme Responsementioning
confidence: 99%
“…Sun and Jahangiri [2] designed a three-dimensional pendulum tuned mass damper (3d-PTMD) to control the multi-directional vibration of the OWT, and it has 10% more damping effect than double TMDs have. Hemmati and Oterkus [3] developed a semi-active TMD for the vibration reduction of OWTs; they used a short-time Fourier transform to adjust the damping system to the instantaneous frequency of the system to achieve a better damping effect. The results showed that the performance of a semi-active TMD with a mass ratio (the ratio of mass of TMD to mass of the structure) of 1% is better than a passive TMD with a mass ratio of 4%.…”
Section: Offshore Wind Turbine (Owt)mentioning
confidence: 99%
“…Also, these controllers are designed to regulate the rotor speed and are not designed for structural vibration/load reduction. Most work on vibration control of wind turbines use external damping devices to reduce unwanted vibrations [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These studies present various passive, semiactive and active structural control using damping devices.…”
Section: Introductionmentioning
confidence: 99%